2019
DOI: 10.22467/jwmr.2018.00528
|View full text |Cite
|
Sign up to set email alerts
|

Extravasation Wound Care in the Neonatal Intensive Care Unit

Abstract: Background: Extravasation injuries occurring in neonates can have severe consequences. Because many clinicians are not familiar with the vesicant-like effect of several commonly used medications, early extravasation wound management can be difficult. We aimed to share our experience with irritant-related and vesicant-related injuries leading to neonatal extravasation wounds. Methods: This retrospective study included 36 premature neonatal patients with extravasation wounds. Patients were classified into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…As explained above, one of the key factors is the type of extravasant. Despite previous studies that illustrated total parenteral nutrition (TPN) as the cause of most lesions after extravasation [ 13 , 20 ], our study found that calcium chloride was responsible for most high-stage wounds ( 56.3%). Less common damages were related to TPN.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…As explained above, one of the key factors is the type of extravasant. Despite previous studies that illustrated total parenteral nutrition (TPN) as the cause of most lesions after extravasation [ 13 , 20 ], our study found that calcium chloride was responsible for most high-stage wounds ( 56.3%). Less common damages were related to TPN.…”
Section: Discussioncontrasting
confidence: 99%
“…We believe that our healing duration in stage 3,4 extravasation lesions was shorter than the one in Cho et al’s previous study; (13.12 days to an average of 18.7 days) despite having more extensive wound sizes ( 7.31cm2 to 2.24 cm2). Based on our data, the cannulation duration at the extravasation injury was longer than the one in the survey conducted by Cho et al (7.87 days to 3.2) [ 13 ]. This proposes a precise observation of the intravenous line site to prevent injury, at least during this time.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…(Khanali Mojen & Varzeshnejad, 2020). Damage to various skin layers results from skin injuries ranging from the epidermis to the underlying layers, and even muscles, as well as tendons (Cho et al, 2019). Skin injuries are caused by different factors which are probably occurred and continue to occur in NICUs Despite the fact that most are avoidable (Grosvenor et al, 2019).…”
Section: Introductionmentioning
confidence: 99%